68.3k views
5 votes
An equation is given.

y = 3x + c


Create an equivalent equation by solving for x in terms of y and c.

User Necrifede
by
7.3k points

2 Answers

6 votes

Answer:

X = (y - c)/3 OR X= (y/3 )- (c/3)

Explanation:

If y = 3x + c

And we are made to make "X" the subject of the formula also known ad solving for "X",all we need to do is

Firstly,subtract both sides by c to leave out only x at one side of the equality sign

Y= 3x + c

Subtracting both sides by c,we have

Y - c = 3x + c - c

y - c = 3x.

Secondly, divide both sides by 3 so as not to have any coefficient for x

(Y - c) ÷ 3 = 3x ÷ 3

(y - c)/3 = x

X = (y - c)/3 OR X= (y/3 )- (c/3)

User Vasiliy Faronov
by
8.0k points
4 votes

Answer: x = 1/3y + 1 /3 c

Explanation:

Hi, to answer this question we have to solve for x:

y =3x +c

3x +c = y

isolating x (the whole term)

3x = y +c

x = (y+c)/3

Applying distributive property

x = (y÷ 3) + (c ÷ 3)

x = 1/3y + 1 /3 c

Feel free to ask for more if needed or if you did not understand something.

User Daniel Ezra
by
6.8k points